Patients’ awareness of their rights: An insight from a teaching hospital in Saudi Arabia: Patients’ awareness of their rights - Madadin, Mohammed; Menezes, Ritesh G.; Almazrua , Abdulaziz A.; Alzahrani , Bandar A.; Alassaf , Maha A.; Al-Hwiesh , Abdullah K.; Usman , Muhammad Shariq (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Knowledge and awareness of patients’ rights are essential to reach the highest quality of care. In 2006, the Saudi Arabian government formulated “The Patients’ Bill of Rights” to ensure that healthcare delivery is at its highest standard. Despite their efforts, several studies revealed patients’ lack of awareness. In this study, we aim to investigate the patients’ awareness of their rights according to the policy of a teaching hospital in Saudi Arabia. Methods: A cross-sectional study was conducted where the participants (n= 384) were in-patients and out-patients of a tertiary care teaching hospital in the Eastern Province of Saudi Arabia. Informed consent was obtained, and confidentiality was maintained. The questionnaire consisted of 23 questions. Data were analyzed using Statistical Package Social Software version 26. Results: Most of the participants were males (70.1%), in-patients (63.3%), and Saudi nationals (84.5%) with a mean age of 32 years. The mean awareness score was satisfactory (>7/14). However, more than half of the participants were unaware of their right to know the risks and benefits of treatment (55.1%), to know the identity of their healthcare providers (61.9%), to deny participation in research (58%), and appoint a healthcare proxy (64.8%). Conclusions: The present study revealed the lack of awareness of certain aspects of patients’ rights that require action in the means of hospital awareness campaigns and educational materials. Further research is required to generalize a consensus on the Saudi population’s level of awareness and consequent steps to optimize the delivery of healthcare in the country.